Intrinsic motivation of preclinical medical students participating in high-fidelity mannequin simulation. (22nd April 2015) - Thoma, Brent; Hayden, Emily M; Wong, Nelson; Sanders, Jason L; Malin, Greg; Gordon, James A
Abstract : Introduction: While medical schools strive to foster students' lifelong learning, motivational theories have not played an explicit role in curricular design. Self-determination Theory is a prominent motivational theory. It posits that perceived autonomy, competence and relatedness foster intrinsic motivation. This study explores the effects of autonomy on intrinsic motivation in medical students participating in high-fidelity mannequin simulation. Methods: A non-randomised crossover trial compared first-year medical students participating in (1) required simulation sessions with predetermined learning objectives and (2) extracurricular simulation sessions with student-directed learning objectives. An adapted Intrinsic Motivation Inventory (IMI) was used to assess intrinsic motivation, perceived autonomy, competence and relatedness. Each participant completed the IMI survey after each type of session. Variables were compared with signed-rank tests. Results: All 22 participants completed the IMI after both types of session. Perceived autonomy was significantly higher during extracurricular simulation (p<0.001), but intrinsic motivation, competence and relatedness were not. Intrinsic motivation correlated with autonomy (RS=0.57 and extracurricular simulation, ES=0.52), competence (RS=0.46 and ES=0.15) and relatedness (RS=0.51 and ES=0.64). The IMI subscales had good internal consistency (Cronbach's α=0.84, 0.90, 0.90 and 0.76 for intrinsic motivation, autonomy, competence and relatedness, respectively). Conclusions: Extracurricular sessions increased students' perceived autonomy, but they were highly intrinsically motivated in both settings. Further study is needed to understand the relationship between perceived autonomy and intrinsic motivation in medical education learning activities. The IMI shows promise as a measurement tool for this work.